Ectopic parathyroid adenoma on sternocleidomastoid muscle: a case report - Shan, HuiMin; Jiang, ZhenPeng; Xu, Jin; Li, JingFa; Zhu, XuSheng (Frontiers in Oncology, 2024)
A 54-year-old woman was admitted to the hospital with a left neck mass. Enhanced CT and ultrasound examinations revealed a lesion in the left sternocleidomastoid muscle. The patient undergone right thyroid lobe resection 8 years ago. Interestingly, the lesion on the sternocleidomastoid muscle, along with the left lobe of the patient’s thyroid, visually appears to form a displaced and complete thyroid in the early Tc-99m-MIBI parathyroid scintigraphy. Combined with Tc-99m-MIBI scintigraphy and abnormal PTH and blood calcium levels, the consideration was given to the lesion in the sternocleidomastoid muscle as an ectopic parathyroid adenoma. Subsequent surgical pathology confirmed this suspicion.